1998
DOI: 10.1074/jbc.273.45.29864
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D Expression Is Controlled Post-transcriptionally via a Phosphatidylinositol 3-Kinase/Akt-dependent Pathway

Abstract: Growth factors elicit their biological effects by activating a complex network of receptors and signaling pathways. Activation of transmembrane tyrosine kinases by serum or polypeptide growth factors results in the transit of cells through the G 1 phase of the cell cycle into S-phase. Several lines of evidence suggest that the D-type cyclins and their associated kinases (Cdks) 1 are among the targets of these growth signals (1). The D-type cyclins, D1, D2 and D3, are closely related proteins whose expression i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
341
2
4

Year Published

1999
1999
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 449 publications
(364 citation statements)
references
References 60 publications
17
341
2
4
Order By: Relevance
“…However, the extent of any role for caspase-9 inhibition in mediating the antiapoptotic e ects of IGF-1 remains to be established and it seems reasonable to expect that other substrates will also be important. As noted above, cyclin D3 can potentiate death by c-Myc (Janicke et al, 1996) and recently this cyclin has been reported to be a substrate for AKT (Muise-Helmericks et al, 1998). It is also conceivable that other Ras e ectors may also be involved in mediating IGF-1-generated survival signals, such as those involving Rho or NF-kB (Lebowitz et al, 1995;Mayo et al, 1997).…”
Section: Regulation By Cytokines and Adhesion Signalsmentioning
confidence: 89%
“…However, the extent of any role for caspase-9 inhibition in mediating the antiapoptotic e ects of IGF-1 remains to be established and it seems reasonable to expect that other substrates will also be important. As noted above, cyclin D3 can potentiate death by c-Myc (Janicke et al, 1996) and recently this cyclin has been reported to be a substrate for AKT (Muise-Helmericks et al, 1998). It is also conceivable that other Ras e ectors may also be involved in mediating IGF-1-generated survival signals, such as those involving Rho or NF-kB (Lebowitz et al, 1995;Mayo et al, 1997).…”
Section: Regulation By Cytokines and Adhesion Signalsmentioning
confidence: 89%
“…Binding of IGF-I or IGF-II to the extracellular portion of the receptor triggers autophosphorylation of the subunits and activation of the tyrosine kinase domain. This phosphorylation permits the activation of intracellular signaling such as the Erk1/ 2 and Akt pathways that induce cell proliferation and inhibit apoptosis (Marte and Downward, 1997;Cardone et al, 1998;Muise-Helmericks et al, 1998;Richards et al, 1998;Baserga, 1999;Surmacz, 2000;Adams et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…AKTs are major downstream targets of growth factor receptors that signal through phosphatidylinositol 3-kinase (Testa and Bellacosa, 2001). Mounting evidence exists that activation of AKT proteins is important in cancer development (Muise-Helmericks et al, 1998;Dimmeler et al, 1999;Khwaja, 1999;Ozes et al, 1999;Mende et al, 2001;Wei et al, 2001). PTEN inhibits AKT activation and works as a tumour suppressor (Testa and Bellacosa, 2001).…”
mentioning
confidence: 99%